Beban Piutang Tak Tertagih yang berpengaruh kepada tingkat Profitabilitas Pada PT Holcim Indonesia Tbk Tahun 2009 - 2017 - Teti Sumarni; Linda Daniati Melinda; Agie Nurmansyah (LPPM POLITEKNIK LP3I BANDUNG, 2020)
This study aims to determine the effect of uncollectible receivables on profitability at PT Holcim Indonesia Tbk. Period 2009 - 2017 Every company is trying to get a large profit and investors want their investment to continue to increase, the company will increase by controlling uncollectible receivables so well that there is an increase in the company's profitability, one of the indicators is a stable profitability (Net Profit Margin) or even always decreases. Researchers use quantitative research methods. The technique used in sampling is Nonprobability Purposive Sampling. Nonprobability Purposive Sampling is a sampling technique with certain considerations. To collect data, use documentation. The analysis technique used in this study is simple linear regression analysis. The effect of uncollectible receivables on the profitability obtained results and conclusions can be made from the calculation results, namely the significance value for uncollectible receivables at share price is 0.003> 0.05. Thus the hypothesis is accepted. it means that the Uncollectible Cost affects the profitability. the magnitude of adjusted R2 value is 0.727 which means that the variability of the dependent variable that can be explained by the variability of the independent variable is 72.7% while the remaining 27.3% is explained by other variables not included in the regression model.